Polygamous Marriages (Study of the Pringsewu Religious Court Number 525/Pdt.G/2020/PA.Prw) - Nuraini, Amartia; Baihaqi, Yusuf; Sukandi, Ahmad (KnE Social Sciences, 2024)
The decision of the Pringsewu Religious Court Number 525/Pdt.G/2020/PA.Prw is a case of an inheritance dispute between the first wife and her three children (plaintiff) and the second wife (defendant) in a polygamous marriage with a man (inheritor). The problem with this decision is that the two plots of land are under the second wife’s name and were purchased when the heir married the second wife. Mediation had been carried out between the first wife and the second wife with their respective attorneys. However, they still could not come up with a definitive solution. The first wife insists she was still married to the inheritor until he died in 2017. Therefore, the list of heirs must still include the first wife and the three children from her marriage to the late inheritor. Meanwhile, the second wife insisted that the land in dispute was the result of her own efforts without any interference from the inheritor, which meant that the second wife assumed that the land in dispute belonged to her. Public understanding regarding the distribution of inheritance in polygamous marriages is still minimal. This research uses a qualitative approach, examining the state of scientific objects and emphasizing the meaning of an object of study. This means there are still many inheritance distribution practices that neither follow the rules stated in Islam nor the law practiced in Indonesia. Keywords: court decision, inheritance, polygamy